Dependence of near field co-seismic ionospheric perturbations on surface deformations: A case study based on the April, 25 2015 Gorkha Nepal earthquake. Issue 5 (1st March 2017) - Sunil, A.S.; Bagiya, Mala S.; Catherine, Joshi; Rolland, Lucie; Sharma, Nitin; Sunil, P.S.; Ramesh, D.S.
Highlights: Rupture as an extended and continuous source for acoustic waves. Directivity of co-seismic ionospheric perturbations (CIP) around the epicenter. Near field CIP over and near the fault plane and geomagnetic field-wave coupling. Abstract: Ionospheric response to the recent 25 April 2015 Gorkha, Nepal earthquake is studied in terms of Global Positioning System-Total Electron Content (GPS-TEC) from the viewpoints of source directivity, rupture propagation and associated surface deformations, over and near the fault plane. The azimuthal directivity of co-seismic ionospheric perturbations (CIP) amplitudes from near field exhibit excellent correlation with east-southeast propagation of earthquake rupture and associated surface deformations. In addition, the amplitude of CIP is observed to be very small in the opposite direction of the rupture movement. Conceptual explanations on the poleward directivity of CIP exist in literature, we show the observational evidences of additional equator ward directivity, interpreted in terms of rupture propagation direction. We also discuss the coupling between earthquake induced acoustic waves and local geomagnetic field and its effects on near field CIP amplitudes. We suggest that variability of near field CIP over and near the fault plane are the manifestations of the geomagnetic field-wave coupling in addition to crustal deformations that observed through GPS measurements and corroborated by Interferometric Synthetic Aperture Radar (InSAR) data sets.